Investigation of cracking behavior in asphalt pavement using digital image processing technology - Jiang, Jie; Xu, Kui; Song, Yanbin; Gao, Ling; Zhang, Jinzhu (Frontiers in Built Environment, 2025)
IntroductionRoad hazards and some traffic accidents are often caused by damage of the performance of the pavement due to cracking of asphalt concrete.MethodsA simulation test was designed to investigate asphalt pavement cracking under different temperature conditions (15°C, 0°C, −5°C, −15°C) with a fixed traffic load strip. Using Gaussian filtering to eliminate texture noise (5 × 5 convolution kernels), extracting continuous crack contours through Canny operator (dual threshold 0.7/0.3), and combining with improved Otsu algorithm (32 × 32 block dynamic threshold) to achieve accurate segmentation under complex lighting conditions; Innovatively introducing a dual parameter system of fractal dimension (box dimension method) and crack rate (crack area ratio) to quantitatively characterize the complexity of crack morphology and degree of damage.ResultsAnd proposed using two crack characteristic parameters, fractal dimension and crack rate, to describe the extension characteristics of cracks. The results indicate that the road surface is more prone to cracking in negative zero temperature environments, with the number and rate of cracks generated at −15°C being much higher than the other three low-temperature environments. Compared to the 15°C environment, the crack rate increased by 18.26%.DiscussionIt has been confirmed that the occurrence and propagation of cracks will be exacerbated in low-temperature environments. The research results provide a theoretical basis and reference significance for the study of pavement crack resistance in cold regions.